2021
DOI: 10.55208/jebe.v15i1.209
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Profitability of Sharia Banking

Abstract: This study aims to examine the factors that affect the Profitability of Islamic banking, such as Corporate Governance (CG), Financing to Deposit Ratio (FDR), Non-Performing Financing (NPF), and Capital Adequacy Ratio (CAR). This research is quantitative. The type of data used in this research is secondary data. Data processing using the multiple linear regression approach. The results showed that Corporate Governance had a significant positive effect on Profitability. Financing to Deposit Ratio has a significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 9 publications
1
2
0
2
Order By: Relevance
“…Most likely because the NPF is too large which causes high FDR but is not able to increase profitability. These results are in accordance with the results of research from Supriadi et al, (2021), Istiqomaha et al, (2021), dan Lohano & Kashif (2019) which found a significant and negative effect between NPF and profitability.…”
Section: Hypothesis Test Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Most likely because the NPF is too large which causes high FDR but is not able to increase profitability. These results are in accordance with the results of research from Supriadi et al, (2021), Istiqomaha et al, (2021), dan Lohano & Kashif (2019) which found a significant and negative effect between NPF and profitability.…”
Section: Hypothesis Test Resultssupporting
confidence: 92%
“…Bank capital besides functioning as a reserve to cover bank losses, if there is excess capital it can be used to provide financing, so that it has the opportunity to increase profits. The results of research on Islamic banks from previous researchers show that CAR has a positive effect on profitability (Supriadi et al, 2021;Javaid & Alalawi, 2018;and Hossain & Khalid, 2018). Likewise in conventional tanks that CAR has a positive effect on profitability (Durguti et al, 2020;Oleiwi et al, 2019;and Lohano & Kashif, 2019).…”
Section: Capital and Profitabilitymentioning
confidence: 96%
“…The NPF of IRBs is too high, so it far exceeds the maximum NPF requirement of 5%. This high NPF has the potential to reduce profitability [6,21]. The high NPF causes other independent variables to be unable to influence financing.…”
Section: Discussionmentioning
confidence: 99%
“…Dalam hal ini, apabila bank mampu memenuhi kewajiban jangka pendek dan apabila bank mampu menyediakan modal pinjaman kepada masyarakat yang cukup besar maka akan meningkatkan image bank dan mendapatkan kepercayaan masyarakat Operating Costs and Operating Income (BOPO) Efisiensi operasional atau BOPO pada dasarnya mempengaruhi kinerja bank, yaitu untuk menunjukkan apakah bank telah menggunakan faktor produksi secara keseluruhan sudah tepat. (Supriadi et al, 2021) Menurut (Sitompul & Nasution, 2019), untuk menunjukkan efisiensi suatu bank adalah dengan menentukan besarnya BOPO, maka harus diketahui biayanya operasi dan pendapatan operasi terlebih dahulu. Lebih Semakin kecil BOPO maka semakin baik karena bank tersebut memiliki tingkat yang tinggi efisiensi yang sangat baik.…”
Section: Tinjauan Teoritisunclassified
“…(Anwar & Arianta, 2019) (Dewi & Bawono, 2022) (Barizi et al, 2021) (Retnowati & Jayanto, 2020) (Afandy et al, 2021) (Wahyuningsih dkk, 2017) Populasi dalam penelitian ini adalah 11 Bank Umum Syariah (BUS) yang telah membuat laporan keuangan tahunan dari tahun 2013 sampai dengan tahun 2021 yang telah dilaporkan dalam laporan publikasi Bank Indonesia melalui website www.ojk.go.id. Dalam penelitian ini tidak menggunakan sampel, melainkan menggunakan populasi karena semua data dalam penelitian ini merupakan data populasi yang berupa data sekunder; (Supriadi et al, 2021) (Fitriana & Musdholifah, 2017).…”
Section: Metode Penelitianunclassified